2021
DOI: 10.1098/rsta.2020.0067
|View full text |Cite
|
Sign up to set email alerts
|

When we can trust computers (and when we can't)

Abstract: With the relentless rise of computer power, there is a widespread expectation that computers can solve the most pressing problems of science, and even more besides. We explore the limits of computational modelling and conclude that, in the domains of science and engineering which are relatively simple and firmly grounded in theory, these methods are indeed powerful. Even so, the availability of code, data and documentation, along with a range of techniques for validation, verification and uncertainty quantific… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 75 publications
(118 reference statements)
0
12
0
1
Order By: Relevance
“…We do not provide a comprehensive review of molecular dynamics applications. We shall spend much less time looking at verification and validation, which are respectively concerned with whether molecular dynamics computer programs are solving the correct equations and how well their output agrees with experimental observations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…We do not provide a comprehensive review of molecular dynamics applications. We shall spend much less time looking at verification and validation, which are respectively concerned with whether molecular dynamics computer programs are solving the correct equations and how well their output agrees with experimental observations [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical models are often approached with scepticism regarding their validity. Particularly in biosciences, verification, validation and uncertainty quantification (VVUQ) become highly important ( Coveney and Highfield, 2021 ). In the context of electrical stimulation, the need for thorough VVUQ is corroborated by problems in the reproducibility of experimental studies, which have been identified in recent research ( Portelli et al, 2018 ; Budde et al, 2019 ; Guette-Marquet et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in previous calls for transparency in COVID‐19 modeling, modelers do not systematically provide their code, [ 104 ] despite the existence of several platforms in which scientists can openly share code and data. [ 105 ] In a transparency assessment, Jalali et al. found that most models do not share their code, [ 106 ] which echoes similar observations about practices in agent‐based modeling across application domains.…”
Section: Discussionmentioning
confidence: 75%